Does fixed income buffer against fraud shocks? - Steven James Lee (Journal of Risk and Financial Management, 2021)
Counterparty risk in the form of investment fraud damages a retiree's nest egg. Does fraud negatively impact portfolios that are both stock and bond-heavy equally? This study uses Monte Carlo analysis within the Trinity Study framework to determine the average reduction in portfolio success of a retiree who experiences fraud. Findings suggest that each incidence of fraud results in a loss of three percentage points in retirement success. However, portfolios containing some bonds (75/25, 50/50, and 25/75) outperform all equity (and all bond) allocations, particularly when fraud is present. On average, each incident of fraud reduces the chance the victim will enjoy a successful retirement by nearly 3%. Various limitations, implications, and future research possibilities are discussed.
Keywords: 330; fraud; fraud shocks; retirement; portfolio success; Monte Carlo